2021
DOI: 10.1055/a-1467-5828
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavin-3’-O-gallate a Black-tea Constituent Blocked SARS CoV-2 RNA dependant RNA Polymerase Active-site with Better Docking Results than Remdesivir

Abstract: Background Replication of SARS-CoV-2 depends on viral RNA-dependent RNA-polymerase (RdRp). Remdesivir, the broad-spectrum RdRp inhibitor acts as nucleoside-analogues (NAs). Remdesivir has initially been repurposed as a promising drug against SARS-CoV-2 infection with some health hazards like liver damage, allergic reaction, low blood-pressure, and breathing-shortness, throat-swelling. In comparison, theaflavin-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Based on molecular docking technology, it has been proved that tea polyphenols, especially theaflavins (TF, TF2B), might inhibit the activities of NSP16 (coronavirus 2′-Omethyltransferase), Angiotensin-converting enzyme 2 (ACE2), RNA replicase (RdRp) and 3C-likeprotease (3CLpro) of SARS-CoV-2, and inhibit the replication and transcription of the virus, thereby preventing the spike protein from attaching to human cells [ [60] , [61] , [62] , [63] ]. In vitro verification confirmed that EGCG in tea could interfere with the binding of SARS-CoV-2 RBD to ACE2 of host cells, or by inhibiting the activity of 3CLpro, thereby blocking the initial invasion process of the virus [ 64 66 ].…”
Section: The Effects Of Tea On Covid-19 and Its Sequelaementioning
confidence: 99%
“…Based on molecular docking technology, it has been proved that tea polyphenols, especially theaflavins (TF, TF2B), might inhibit the activities of NSP16 (coronavirus 2′-Omethyltransferase), Angiotensin-converting enzyme 2 (ACE2), RNA replicase (RdRp) and 3C-likeprotease (3CLpro) of SARS-CoV-2, and inhibit the replication and transcription of the virus, thereby preventing the spike protein from attaching to human cells [ [60] , [61] , [62] , [63] ]. In vitro verification confirmed that EGCG in tea could interfere with the binding of SARS-CoV-2 RBD to ACE2 of host cells, or by inhibiting the activity of 3CLpro, thereby blocking the initial invasion process of the virus [ 64 66 ].…”
Section: The Effects Of Tea On Covid-19 and Its Sequelaementioning
confidence: 99%
“…Bioinformatics and molecular docking studies by Maiti and Banerjee demonstrated that the TF gallate exhibits greater binding affinity to the SARS-CoV-2 S protein than does hydroxychloroquine (HCQ), thus indicating its superior inhibitory activity compared to that of HCQ [107] . Theaflavin-3’- O -gallate (TFMG) is an enriched compound in black tea that has been demonstrated to block the active portion of SARS-CoV-2 RdRp with better docking than that of remdesivir [68] . Additionally, a virtual screening and molecular dynamics simulation study revealed that TF3 and TF2a exhibit the highest binding affinities towards RdRp, M pro , and PL pro targets on SARS-CoV-2 [5] .…”
Section: Anti-sars-cov-2 Compounds In Teamentioning
confidence: 99%
“…Interference with SARS-CoV-2 invasion by inhibiting TMPRSS2 [66] OFA M pro Interference with SARS-CoV-2 replication by inhibition of M pro [6] TFs M pro /PL pro /RdRp Interference with M pro , PL pro , and RdRp to block SARS-CoV-2 replication [5,[67][68] WTSNF NF-κB pathway Reduction in the levels of IL-6, IL-1β, IL-17, IL-8, TNF-α, and IFN-γ [69] EGCG: (-)-epigallocatechin-3-gallate; GCG: (-)-gallocatechin gallate; LLPS: Liquid-liquid phase separation; OFA: Oolonghomobisflavan A; TA: Tannic acid; TFs: theaflavins; WTSNF: white-tip silver needle flavonoids.…”
Section: Tmprss2mentioning
confidence: 99%
“…anticancer [11,12], and antitumour [13] activities and can protect against liver and kidney damage [14,15] and enhance immunity [16]. In addition, polyphenols in black tea have been reported to have antioxidant, anticancer, lipid homeostasis [17,18], antidiabetic [19], intestinal ora promotion, and obesity suppression [20] health effects.…”
Section: Introductionmentioning
confidence: 99%